2021
DOI: 10.1101/2021.05.06.442800
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The influence of the respiratory cycle on reaction times in sensory-cognitive paradigms

Abstract: Behavioural and electrophysiological studies point to widespread influence of the state of respiration on brain activity and cognitive performance. Still, the prevalence and relevance of such respiratory-behavioural relations in typical sensory-cognitive tasks remain unclear. We here used a battery of six tasks probing sensory detection, discrimination and short-term memory to address the questions of whether and by how much behaviour covaries with the respiratory cycle. Our results show that participants tend… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…For instance, in moments of suspense, viewers might be "holding their breath" and thus changing the dynamic of heart rate, which is closely linked to breathing 56 . Breathing seems to align to the timing of a behavioral task 57 , but here participants were not asked to do anything specific during viewing. Generally, studies that show correlated breathing involve some concurrent physical activity such as singing 44 , speaking 58 or dancing 43 and correlation is not observed during passive listening to speech 59 , though some effects have been found when listening to music 39 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in moments of suspense, viewers might be "holding their breath" and thus changing the dynamic of heart rate, which is closely linked to breathing 56 . Breathing seems to align to the timing of a behavioral task 57 , but here participants were not asked to do anything specific during viewing. Generally, studies that show correlated breathing involve some concurrent physical activity such as singing 44 , speaking 58 or dancing 43 and correlation is not observed during passive listening to speech 59 , though some effects have been found when listening to music 39 .…”
Section: Discussionmentioning
confidence: 99%
“…The influence of respiration on neuronal rhythms in brain areas involved in cognitive and affective functions suggest that the act of breathing could influence cognition and emotion at a behavioral level. This has now been confirmed in several studies showing that cognitive and affective functions are significantly modulated by respiration [3,26,31,37,39,56] (for recent reviews see: [27,28,48]). How respiration drives this seemingly brainwide rhythm is not fully understood.…”
Section: The Influence Of Breathing On Brain Activity and Functionmentioning
confidence: 66%
“…Active alignment of respiration to a task context was also observed by Johannknecht and Kayser (2021), who subjected participants to five different sensory detection and discrimination tasks and a short-term memory tasks. The analysis of task performance in relation to the respiratory cycle showed that participants tended to align their respiratory cycle to the timing of stimuli and their own response times.…”
Section: Respiration Brain Activity and Cognitionmentioning
confidence: 73%
“…Since the first report of respiratory modulation of delta and gamma oscillations in a nonolfactory part of the mouse neocortex (Ito et al, 2014), a rapidly growing number of publications confirmed the initial findings in both animals and humans. Studies in humans revealed that, as a functional consequence of respiratory modulation of brain activity, cognitive and affective functions are modulated by the respiratory rhythm (Arshamian, Iravani, Majid & Lundstrom, 2018;Grund et al, 2021;Johannknecht & Kayser, 2021;Nakamura, Fukunaga, & Oku, 2018;Perl et al 2019;Zelano et al 2016) (for a recent review see : Heck, Kozma, & Kay, 2019).…”
Section: Respiration Brain Activity and Cognitionmentioning
confidence: 99%